Detection and Analysis of Lysozyme Activity in some Tuberous Plants and Calotropis Procera’s Latex - Palani*, M. Sakthivel, N. Karthikeyan; P. (Journal of Phytology, 2010)
Tuber extract of all the plant species used in the study exhibited lysozyme activity confirming the ubiquitous presence of lysozyme in plants. Among the different plants screened for protein content the tuber extract of Solanum tuberosum showed highest buffer soluble protein while tuber extract of Raphanus sativus showed the lowest protein content in sodium acetate buffer (50 Mm; pH 5.0). Tuber extract of Raphanus sativus showed highest lysozyme activity among all the plant species tested in this study and the activity was increased when the tuber was extracted with sodium phosphate buffer (50mM; pH 7.0). The lowest lysozyme was observed with tuber extract of Daucus carota in phosphate buffer (50mM; pH 7.0). The latex of the tropical species Calotropis procera is well known for being a rich source of the lysozyme. Lysozyme of Calotropis procera latex is not thermo labile. It did not lose much of its activity when the latex was incubated at different temperatures for 24 hours. A positive pointer for purification of this enzyme in future. Calotropis procera lysozyme can be was specifically isolated and purified from the whole latex with ammonium sulphate precipitation with 95% saturation. Calotropis procera lysozyme retained its activity even after precipitation with ammonium sulphate and dialysis and could hydrolyse the cell wall of Micrococcus lysodeikticus. Key words: Micrococcus lysodeikticus, Tuberous Plants, Latex, Ammonium sulphate precipitation, Polyacrylamide gel electrophoresis <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">M. Sakthivel et al. Detection and Analysis of Lysozyme Activity in some Tuberous Plants and Calotropis Procera’s Latex. J Phytol 2/11 (2010) 65-72.